The Gendering of Irish and Caribbean Food/Land Crises in Children's Novels by Marita Conlon-McKenna and James Berry. Issue 1 (May 2019) - Houlden, Kate; Gunne, Sorcha
Abstract : Marita Conlan-McKenna's Under the Hawthorne Tree (1990) and James Berry's Ajeemah and His Son (1991) are children's novels that address foundational national or regional trauma (dealing with transatlantic slavery and the Irish potato famine respectively). Both employ historical fictive modes to bring the nineteenth century to life, in the process illustrating the extractive capitalism at the heart of the colonial endeavour. Links between Ireland and the Caribbean have long existed, Hilary Beckles observing the persistent characterization of the Irish as 'one-dimensional colonial characters […] battered and bruised by a triumphant imperial Englishness that viewed them as "baggage" along the route from Cork and Limerick through Bristol to Boston and Barbados' (Beckles ix). Expanding on this sense of Ireland and the Caribbean as jointly tethered to global imperial trends, this article focuses on the role of food and consumption, arguing that these novels make clear the ongoing role of food scarcity and land control within the cyclical crises of capitalist expansion. Ajeemah and His Son reinforces the importance of land ownership in Jamaica as its protagonist falls in line with the values of the society he has been thrust into, while Under the Hawthorne Tree frames famine as a representative crisis of the world-system.